Migração involuntária como fator de risco à saúde mental - Martins-Borges, Lucienne (REMHU, Revista Interdisciplinar da Mobilidade Humana, 2013)
O deslocamento forçado de pessoas é um dos fenômenos que podem ser relacionados a conflitos políticos e sociais, guerras e catástrofes naturais. Essas partidas não-planejadas são frequentemente acompanhadas de sofrimento psicológico diretamente ligado às perdas e ao traumatismo ao qual foram submetidas. Este artigo tem por objetivo apresentar observações realizadas no Serviço de Atendimento Psicológico Especializado aos Imigrantes e Refugiados (Sapsir), da Universidade Laval, Canadá. O trabalho clínico desenvolvido com pessoas oriundas de mais de 40 nacionalidades permitiu ressaltar quadros psicopatológicos mais frequentemente observados e estabelecer períodos críticos do processo de adaptação que tendem a expor tais pessoas a uma maior vulnerabilidade psicológica. Essas observações permitem pensar em políticas de acolhimento e de atendimento (saúde e social) de refugiados, que permitam prevenir um maior sofrimento psíquico e contribuir para uma melhor adaptação. The forced displacement of people, known as refugees or involuntary immigrants, is one of the phenomena related to political and social conflicts, wars and natural catastrophes. These unplanned and often undesired departures are often followed by psychological suffering directly related to the losses and to the trauma to which they have been exposed before and after the migration. Those difficulties can be represented by bureaucratic barriers, obstacles to the reconstruction of a professional and family life, communication difficulties, cultural differences, family roles’ inversions and so on. This article’s main goal is to present observations made at the Service of Specialized Psychological Attention for Immigrants and Refugees (Sapsir), at the Laval University, Québec, Canada. The clinical work developed with people from more than 40 nationalities has ade it possible to highlight psychopathological symptoms more often observed, and establish critical periods in the adaptation process which tend to expose such people to a higher psychological vulnerability. These observations allow us to design policies for sheltering and (health and social) attention for refugees, making it possible to prevent a more serious psychic suffering and, consequently, to contribute for a better adaptation and integration. Todos os artigos da revista REMHU n. 40 estão disponíveis no site SciELO Brasil (www.scielo.br/remhu).All articles of the journal REMHU n. 40 are available online for free: SciELO Brasil (www.scielo.br/remhu).